Maternal characteristics and pregnancy outcomes of hospitalized pregnant women with SARS‐CoV‐2 infection in South Africa: An International Network of Obstetric Survey Systems‐based cohort study. Issue 3 (16th September 2021) - Budhram, Samantha; Vannevel, Valerie; Botha, Tanita; Chauke, Lawrence; Bhoora, Shastra; Balie, Gaynor M.; Odell, Natalie; Lombaard, Hennie; Wise, Amy; Georgiou, Chrysanthi; Ngxola, Nondumiso; Wynne, Emma; et al.
Abstract: Objective: To describe risk factors and outcomes of pregnant women infected with SARS‐CoV‐2 admitted to South African healthcare facilities. Methods: A population‐based cohort study was conducted utilizing an amended International Obstetric Surveillance System protocol. Data on pregnant women with SARS‐CoV‐2 infection, hospitalized between April 14, 2020, and November 24, 2020, were analyzed. Results: A total of 36 hospitals submitted data on 673 infected hospitalized pregnant women; 217 (32.2%) were admitted for COVID‐19 illness and 456 for other indications. There were 39 deaths with a case fatality rate of 6.3%: 32 (14.7%) deaths occurred in women admitted for COVID‐19 illness compared to 7 (1.8%) in women admitted for other indications. Of the women, 106 (15.9%) required critical care. Maternal tuberculosis, but not HIV co‐infection or other co‐morbidities, was associated with admission for COVID‐19 illness. Rates of cesarean delivery did not differ significantly between women admitted for COVID‐19 and those admitted for other indications. There were 179 (35.4%) preterm births, 25 (4.7%) stillbirths, 12 (2.3%) neonatal deaths, and 162 (30.8%) neonatal admissions. Neonatal outcomes did not differ significantly from those of infected women admitted for other indications. Conclusion: The maternal mortality rate was high among women admitted with SARS‐CoV‐2 infection and higher in women admitted primarily for COVID‐19 illness with tuberculosis being the only co‐morbidity associated with admission. Synopsis: A multicenter, observational study describing the risk factors and pregnancy outcomes of women admitted with SARS‐CoV‐2 infection in South Africa, a low‐ and middle‐income country.